Enriching Vermicompost Using P-solubilizing and N-fixing Bacteria under Different Temperature Conditions. Issue 2 (19th January 2017) - Alikhani, Hossein Ali; Hemati, Arash; Rashtbari, Mehdi; Tiegs, Scott D.; Etesami, Hassan
ABSTRACT: In the present study we evaluated changes in phosphorus (P), nitrogen (N), and humic acid (HA) contents of vermicompost (VC) in response to temperature increases, and inoculation with N2 -fixing and P-solubilizing microbes. Inoculants of Pseudomonas and Azotobacter were prepared and used to inoculate VC that was kept at 28 and 41 °C. Biological and chemical parameters of the VC were evaluated at 0, 20, 40, and 60 days. As incubation duration increased, bacterial population, N, available P, and HA content increased while organic carbon and pH decreased. These changes were most rapid during the initial 40 days of the experiment, and slowed subsequently. Increasing temperature from 28 to 41 °C reduced bacterial population and the efficiency of these bacteria in improving VC quality. Overall, our results indicate that inoculation of VC with microbes holds promise as a means of increasing the quality of VC, while our increased temperature treatment was less effective.